Straightforward Synthesis of Triester-Substituted Pyrrolizidines by a Three-Component Reaction of β,γ-Unsaturated α-Keto Esters, Proline, and Maleates - Chen, Lian-Mei; Liu, Zhi-Hui; Nie, Xu-Feng; Guo, Xiao-Qiang; Kang, Tai-Ran (Synlett, 2018)
A three-component reaction of β,γ-unsaturated α-keto esters, proline, and dialkyl maleates has been developed. This reaction provides pyrrolizidine derivatives containing three ester groups and a styrenyl group, as well as a quaternary center, in moderate to good yields and with good to excellent diastereoselectivities.
Keywords: pyrrolizidines; keto esters; proline; maleate esters; multicomponent reaction; 1,3-dipolar cycloaddition